PENGARUH KATALIS ASAM SULFAT PADA SINTESIS NITROSELULOSA TERHADAP DERAJAT SUBSTITUSI - Fitriannoor Fitriannoor; Taufiqur Rohman Taufiqur Rohman; Mahmud Mahmud (Universitas Lambung Mangkurat, 2022)
Effect of sulfuric acid as catalyst due to synthesis of nitrocellulose from pure cellulose towards substitusion degree had been done. The purpose of this research are to find FT-IR absorbance and substitution degree. Nitrocellulose wassynthesized using nitration method in a mixture nitric acid, sulfuric acid and water then cooled at 5OC - 15OC for 60 minutes. Results is showed that nitrocellulose synthesized has FT-IR character that the formation nitro functional group (-NO2) sharp peak at 1635 cm-1 were subtituted completely. However the peak at 1361 cm-1 and 1288 cm-1 nitro functional group (-NO2) incompletely substituted because peak is not sharp. So two hydroxyl functional group peak (-OH) at 3201 cm-1 and 3424 cm-1. Concluded, substitution degree using absorbance ratio from FT-IR spectrum is 2,89.